La violencia política contra las mujeres y su incidencia en la afectación de los derechos. - Coello Ibarra, Yeseña Mishell (2022)
In this research project, the objective of this research project is a legal, doctrinal and critical analysis of political violence agamst women and its incidence in their political role and thus propose a legal reform to the Código Orgánico Integral Penal, for which a descriptive field investigation was used towards professional women of law who are immersed in political parties, through an interview, the content could be analyzed, finding in such a way that women involved in politics, the content found could be analyzed in such a way that women involved in politics; in this study, we have shown that political violence against women was evidenced that rape against women is evidenced in the persistence of discriminatory stereotypes to which they are exposed mainly in social networks with offensive words, physical and emotional abuse in such a way limiting their participation and access to positions public, for which it was considered necessary to enact laws that guarantee the participation of women.